Reforming the Public Pension System in the Russian Federation - Eich, Frank; Gust, Charleen; Soto, Mauricio (Washington, D.C. : International Monetary Fund, 2012)
Pension reform is a key policy challenge in Russia. This paper examines how pension spending could increase in Russia in the absence of reforms, quantifies the impact of some recent proposals, and suggests some alternatives that would ensure public pension benefits - relative to wages - not fall from current levels while containing spending.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet